2016
DOI: 10.1111/add.13666
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study designs examining social context and smoking: scientific challenges and considerations

Abstract: Commentary to: http://onlinelibrary.wiley.com/doi/10.1111/add.13503/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…In our laboratory, we are beginning to examine smoking and cigarette craving experiences in a variety of social settings, including interactions among non‐romantic friends (smoking buddies) and intimate partners. We also agree with Dr Harakeh's suggestion to examine interactions via social media related to smoking and Dr Graham's recommendation to evaluate effects across different levels of socio‐economic status .…”
supporting
confidence: 56%
See 2 more Smart Citations
“…In our laboratory, we are beginning to examine smoking and cigarette craving experiences in a variety of social settings, including interactions among non‐romantic friends (smoking buddies) and intimate partners. We also agree with Dr Harakeh's suggestion to examine interactions via social media related to smoking and Dr Graham's recommendation to evaluate effects across different levels of socio‐economic status .…”
supporting
confidence: 56%
“…We concluded that understanding of smoking will remain incomplete if investigators continue to rely entirely upon laboratory research conducted while individuals participate in isolation . It was both striking and heartening to us to find unanimity among the commentators in their support of our position . They also identified a number of areas where they believe social psychological factors can play a role in understanding smoking.…”
mentioning
confidence: 92%
See 1 more Smart Citation